Pengaruh Kebisingan Kegiatan Pengelasan terhadap Daya Hafal Al-Qur’an Santri Pondok Pesantren Fathul Mu’in Ali Masykur Wonosobo - Fanguna, Arina Mayang; Hasanah, Nurul (Al-DYAS, 2023)
Besides learning and thingking, memorizing is also part of the process of growingbrain tissue. But a person’s memorization can change according to the cobditions of the surrounding environment, one of the environmental conditions that can affect a person’s memorization is noise. The purpose of this study was to determine the effect of noise on students’ Al-Qur’an memorization. The method used is the experimental method with a sample of 5 students who memorize the Al-Qur’an. The research was carried out by varying the surrounding environmental conditions, theresearcher compared the number of students’ memorization when the environmental conditions were quiet with noisy environmental conditions. The result of this study prove that noise can reduce the memorization of students.